Child Soldier Stories and their Fictions. Issue 1 (2nd January 2016) - Mastey, David
Abstract : In this essay I examine child soldier stories, one of the most popular and critically successful genres of African writing in the United States in recent years. They are unique in some respects, but many publishers and US readers are already familiar with their most basic themes. The success of the genre owes much to the fact that it resembles an existing book marketing category known as misery literature. Publishers recognize that child soldier stories may (and in some cases do) generate similar levels of interest and profitability. However, I argue that they are not bound by the same strict distinctions between fantasy and reality. Many US readers associate the genre – and the practice of child soldiering more generally – with Africa. Consequently, child soldier stories are treated as evidence of a continent-wide epidemic that largely exists in the imaginations of its US audience.